Why Do People With Self-Control Forgive Others Easily? The Role of Rumination and Anger - Kong, Fanchang; Zhang, Haibo; Xia, Haishuo; Huang, Bo; Qin, Jingkuan; Zhang, Yan; Sun, Xiaojun; Zhou, Zongkui (Frontiers in Psychology, 2020)
Previous research shows that self-control predicts forgiveness, but few studies have investigated the internal mechanism of this link. The current study explored the effects of rumination and anger on the relationship between self-control and forgiveness. A total of 580 college students recruited from three universities in Wuhan completed the self-control, rumination, anger, and trait forgiveness scales. Results showed that self-control was positively correlated with forgiveness (r = 0.34, p < 0.001). Rumination (β = 0.08, p < 0.05) and anger (β = 0.13, p < 0.05) mediate the relationship between self-control and forgiveness. Moreover, a serial mediation effect of rumination and anger was observed between self-control and trait forgiveness (β = 0.02, p < 0.05). These findings suggest that self-control may impair individuals’ rumination. Moreover, less rumination may restrain anger and consequently increase forgiveness.